Poetics of Friction - Nadja Ben Khelifa; Étienne Allaix; Jörg Sternagel (Performance Philosophy)
What are the problems in our current lifeworld? And how can they be addressed, worked on (or even be solved)? What are the possibilities and difficulties of Performance Philosophy to contribute to reflections on the crisis-ridden, everyday situations we are in, with our very embodied existences, and with our thoughts, fears, hopes (and even prayers), inside and outside art and academia? Called by these questions, our panel attempts to collaboratively work on corresponding responses within a poetics of friction that is rehearsed, acted out, and tried out in a setting where forces come into play that resist relative motions of solid approaches and beliefs sliding against each other: Whereas the three panelists – a multimedia artist, a cultural theorist, and a philosopher – call with their spoken words, screened images and handout materials, the members of the audience respond to these calls: Like the wheel that needs the concrete surface against its rubber to spin in movement, or the piece of wood that needs the wooden stick rotating against its bark to spark a flame, members of Performance Philosophy need frictions with which both Performance artists and Philosophy scholars slide against each other to spin, to move, to carry on, to reflect, to struggle, to doubt, to aim, to spark flames of inspiration. While the sources of such an inspiration are manifold, three of them come into movement and display during the rehearsal: (1) excavation, (2) meaning, and (3) sense.